The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1111/j.1460-9568.2007.05906.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype of V2‐derived interneurons and their relationship to the axon guidance molecule EphA4 in the developing mouse spinal cord

Abstract: The ventral spinal cord consists of interneuron groups arising from distinct, genetically defined, progenitor domains along the dorsoventral axis. Many of these interneuron groups settle in the ventral spinal cord which, in mammals, contains the central pattern generator for locomotion. In order to better understand the locomotor networks, we have used different transgenic mice for anatomical characterization of one of these interneuron groups, called V2 interneurons. Neurons in this group are either V2a inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
163
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(180 citation statements)
references
References 66 publications
(131 reference statements)
12
163
2
Order By: Relevance
“…This contrasts with RCs, which appear to be homogeneously derived from V1 interneurons (Sapir et al, 2004). Alternative ventral interneurons with ipsilateral inhibitory axons are derived from the V2b group (Al-Mosawie et al, 2007;Lundfald et al, 2007). The possible derivation of some populations of IaINs from the V2b group is currently under investigation.…”
Section: Neonatal V1-derived Ia Inhibitory Interneurons and The Ontogmentioning
confidence: 93%
See 1 more Smart Citation
“…This contrasts with RCs, which appear to be homogeneously derived from V1 interneurons (Sapir et al, 2004). Alternative ventral interneurons with ipsilateral inhibitory axons are derived from the V2b group (Al-Mosawie et al, 2007;Lundfald et al, 2007). The possible derivation of some populations of IaINs from the V2b group is currently under investigation.…”
Section: Neonatal V1-derived Ia Inhibitory Interneurons and The Ontogmentioning
confidence: 93%
“…Pitx2 neurons are also already recognizable in early embryos (E12) within the V0 population (Zagoraiou et al, 2009). V2 interneurons diversify into excitatory Chx10-positive V2a and inhibitory GATA3-positive V2b interneurons (Lundfald et al, 2007). Finally, V3 interneurons also diversify in embryo into two groups with distinct migration patterns becoming located in two different spinal cord regions (Zhang et al, 2008).…”
Section: Diversification Of V1 Interneuronal Populationsmentioning
confidence: 97%
“…The V2a interneurons constitute a subpopulation of the V2 class and express Chx10. The Chx10 neurons are exclusively glutamatergic and project ipsilaterally (Al-Mosawie et al, 2007;Lundfald et al, 2007). Recently, we have shown that left-right alternation is disrupted in transgenic mice in which Chx10 neurons have been selectively ablated by diphtheria toxin A, whereas alternation between flexors and extensors on the same side remains intact (Crone et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In the mouse spinal cord, two broad populations of excitatory INs have been identified by their intraspinal axonal trajectories and developmental expression of molecular markers: (1) ipsilaterally projecting INs that express the transcription factors HB9 (Hinckley et al, 2005;Wilson et al, 2005), Chx10 (AlMosawie et al, 2007;Lundfald et al, 2007), or Sim1 (Zhang et al, 2008; J. C. Glover, unpublished observations); and (2) contralaterally projecting INs (CINs) that express the transcription factors Evx1 Pierani et al, 2001;Lanuza et al, 2004) or Sim1 (Zhang et al, 2008;Hägglund et al, 2010). It is clearly established in the adult cat that excitatory CINs receive inputs from pontine reticulospinal neurons (Jankowska et al, 2009 and references therein).…”
Section: Introductionmentioning
confidence: 99%